Mfn2 is responsible for inhibition of the RIG-I/IRF7 pathway and activation of NLRP3 inflammasome in Seneca Valley virus-infected PK-15 cells to promote viral replication - Deng, HuiDan; Zhu, Song; Zhu, Ling; Sun, Jing; Ding, YuChun; Li, FengQin; Jian, ZhiJie; Zhao, Jun; Deng, LiShuang; Deng, JunLiang; Deng, YouTian; Guo, HongRui; et al. (Frontiers in Immunology, 2022)
Seneca Valley virus (SVV), a non-enveloped positive single-stranded virus can cause vesicular disease in swine. However, the mechanisms by which SVV activates an innate immune response remain unknown. Mitofusin-2 (MFN2), a mitochondria-shaping protein regulating mitochondrial fusion and fission, plays a crucial role in innate immune responses. But, the roles of Mfn2 in SVV infection have not been elucidated. Here, we show that SVV inhibited Mfn2 expression and NLRP3 inflammasome, activating RIG-I/IRF7 signaling pathway to increase IFN-λ3 expression. Overexpression of Mfn2 inhibited RIG-I/IRF7 signaling pathway, thus decreasing IFN-λ3 expression and promoting SVV replication. Interestingly, overexpression of Mfn2 also activated NLRP3 inflammasome but did not inhibit SVV proliferation. That may mean the RIG-I/IRF7 signaling pathway plays a more important role in SVV proliferation in PK-15 cells. This study could provide important insights into the modulation of host metabolism during SVV infection and provide a strong theoretical basis for a better understanding of the pathogenic mechanism and immune activation mechanism of SVV.